Delivery Truck Drivers' Work Outside Their Cabs: Ergonomic Video Analyses Supplemented with National Accident Statistics. Issue 3 (15th January 2014) - Reiman, Arto; Putkonen, Ari; Nevala, Nina; Nyberg, Mika; Väyrynen, Seppo; Forsman, Mikael
Abstract Delivery truck drivers' work contains various physically and psychosocially demanding work situations. Fifteen drivers' and 8 other stakeholders' identifications of such work situations were examined by video analyses in this study. The identifications were analyzed in‐depth by the researchers and compared with statistics on 3, 507 accidents in the Finnish trucking industry. The aim was to determine what kind of identifications were made and to what degree the identifications coincided among the participants and with the accident statistics. The drivers' identifications differed from the statistics data. The statistics showed a significantly higher relative frequency of movement‐related situations. However, the identifications also included risks for future workload‐related musculoskeletal disorders. Most commonly, these were emphasized during manual materials handling. The participation of different interest groups seems to increase the amount of relevant information obtained. Nonetheless, the age of the evaluator seems not to affect the analyses.